Geomorphic controls on floodplain sediment and soil organic carbon storage in a Scottish mountain river. Issue 1 (13th November 2019) - Swinnen, Ward; Daniëls, Teun; Maurer, Eline; Broothaerts, Nils; Verstraeten, Gert
Abstract: River floodplains constitute an important element in the terrestrial sediment and organic carbon cycle and store variable amounts of carbon and sediment depending on a complex interplay of internal and external driving forces. Quantifying the storage in floodplains is crucial to understand their role in the sediment and carbon cascades. Unfortunately, quantitative data on floodplain storage are limited, especially at larger spatial scales. Rivers in the Scottish Highlands can provide a special case to study alluvial sediment and carbon dynamics because of the dominance of peatlands throughout the landscape, but the alluvial history of the region remains poorly understood. In this study, the floodplain sediment and soil organic carbon storage is quantified for the mountainous headwaters of the River Dee in eastern Scotland (663 km 2 ), based on a coring dataset of 78 floodplain cross‐sections. Whereas the mineral sediment storage is dominated by wandering gravel‐bed river sections, most of the soil organic carbon storage can be found in anastomosing and meandering sections. The total storage for the Upper Dee catchment can be estimated at 5.2 Mt or 2306.5 Mg ha ‐1 of mineral sediment and 0.7 Mt or 323.3 Mg C ha ‐1 of soil organic carbon, which is in line with other studies on temperate river systems. Statistical analysis indicates that the storage is mostly related to the floodplain slope and the geomorphic floodplain type, which incorporates the characteristic stream power, channel morphology and the deposit type. Mapping of the geomorphic floodplain type using a simple classification scheme shows to be a powerful tool in studying the total storage and local variability of mineral sediment and soil organic carbon in floodplains. © 2019 John Wiley & Sons, Ltd. Abstract : The floodplain sediment and soil organic carbon storage is quantified for a Scottish Highland river (Upper Dee). The high variability in sediment and soil organic carbon storage can be related to variability in local floodplain morphology and spatial differences in geomorphic activity. The construction of scaling relationships shows to be a useful tool to gain insight in regional storage differences.